SEMANTIK NAMA DIRI DALAM MASYARAKAT MELAYU TAMIANG DI KABUPATEN ACEH TAMIANG (SEMANTIC OF PERSONAL NAMES OF TAMIANG MALAY COMMUNITY IN ACEH TAMIANG REGION) - Halimatussakdiah Halimatussakdiah; Mulyadi Mulyadi (Metalingua: Jurnal Penelitian Bahasa, 2021)
AbstractThis study aimed to find the types of personal names (nama diri) in the Tamiang of Malay community (MT) and analyze the semantics of the names in the MT community with the Natural Semantic Metalanguage (NSM) approach. This research employed qualitative paradigm. The data sourced by interviews with native speakers and written documents about the MT community. Data collected by listening and record. Data were analyzed using an interactive model by considering the default meaning table as a means of grouping the analyzed self names. Furthermore, this type of personal name is replicated (paraphrasing) so that the meaning of the type of personal name in the MT community is found. Personal names in the Tamiang of Malay community have various names and indicate the origin of all of the names based on their birth order names, names based on physical references and characteristics, personal names in cultural traditions such as birth traditions, marriage and so on. Naming comes from phenomena in society. The original meaning that is combined in the MT personal names implication are someone, say and do from semantic primitive elements.